Gender Hate Online
XXIV, 281 p. 33 illus., 31 illus. in color.
Keywords: Gender Hate Online addresses the dynamic nature of misogyny: how it travels, what technological and cultural affordances support or obstruct this and what impact reappropriated expressions of misogyny have in other cultures. It adds significantly to an emergent body of scholarship on this topic by bringing together a variety of theoretical approaches, while also including reflections on the past, present, and future of feminism and its interconnections with technologies and media. It also addresses the fact that most work on this area has been focused on the Global North, by including perspectives from Pakistan, India and Russia as well as intersectional and transcultural analyses. Finally, it addresses ways in which women fight back and reclaim online spaces, offering practical applications as well as critical analyses. This edited collection therefore addresses a substantial gap in scholarship by bringing together a body of work exclusively devoted to this topic. With perspectives from a variety of disciplines and geographic bases, the volume will be of major interest to scholars and students in the fields of gender, new media and hate speech. Debbie Ging is Associate Professor of Media Studies in the School of Communications at Dublin City University, Ireland. Eugenia Siapera is Associate Professor of Digital and Social Media and Deputy Director of the Institute for Future Media and Journalism in the School of Communications at Dublin City University, Ireland.